Stylistic Fronting as Remnant Movement1. (21st July 2016) - Ott, Dennis
Abstract: This paper presents a novel analysis of Stylistic Fronting (SF) in Icelandic. It is argued that SF is not a head‐movement operation, but rather phrasal movement to subject position. Typically, however, independent factors require evacuation movements prior to raising, in which case the fronted phrase moves as a remnant category. It is shown that this approach can account for a variety of otherwise puzzling properties of SF.